Perbedaan Efektivitas Senam Otak terhadap Peningkatan Fungsi Kognitif antara Lansia Laki-Laki dan Perempuan - Fatsiwi Nunik Andari; Muhammad Amin; Yeta Fitriani (Jurnal Keperawatan Silampari, 2018)
The purpose of this study was to determine differences in cognitive function between men and women of elderly after being given brain gym intervention in patients with cognitive impairment. This research used experiment method, using Quasi experiment design with pre and posttest design. The results showed that there was a difference of cognitive function between men and women of elderly after giving brain exercise intervention with P value = 0,025. Conclusion, there was a difference in the effectiveness of brain gym on improving cognitive function between men and women of elderly. Brain gym is more effective for improving cognitive function in elderly men. Keywords :Brain Gym, Cognitive Function, Elderly